Interventions for burnout and well-being in homelessness staff: A systematic scoping review - Lauren Ng; Emily Adams; David Henderson; Eddie Donaghy; Stewart W. Mercer (PLoS ONE, 2025)
Background Homelessness staff often experience high job demands, limited resources, and significant emotional strains; with high levels of burnout, stress, and trauma being common within the workforce. Despite growing recognition of these issues, limited literature exists on interventions to address them. This study aims to conduct a systematic scoping review to map and identify interventions aimed at improving well-being and reducing burnout among homelessness staff. Methods All eligible studies needed to include an intervention addressing burnout and/or well-being in homelessness staff, published in English with primary data. Evidence sources were left open with no data restrictions. Following protocol registration, a systematic search of five electronic databases (Medline, APA PsychInfo, Global Health, ASSIA, CINAHL) and Google Scholar was conducted. Studies were double-screened for inclusion. Methodological quality was assessed using the Mixed Methods Appraisal Tool. Results Of the 5,775 screened studies, six met the inclusion criteria: two peer-reviewed and four non-peer-reviewed publications. No studies were retrieved from Google Scholar. The included studies comprised four quantitative non-randomised designs, one randomised controlled trial, and one mixed-methods study. All included studies were complex interventions. Three were therapy-based, two included supervision, and two were one-time educational sessions. Most were conducted in the United States (n = 4), with two in the United Kingdom. The total pooled sample was 347 participants, though four studies were missing demographic data (age and gender). The studies used heterogenous measures and outcomes. Limitations included restrictions to English-only publications, potential gaps in capturing well-being measures, and a limited grey literature scope. Conclusion There is a lack of research on well-being and burnout interventions in frontline homelessness staff. Identified studies were generally low quality, using heterogenous measures and outcomes to assess well-being and burnout, limiting the generalisability of findings. Future research should employ more robust study designs with standardised measures and outcomes.